(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate health-promoting behaviors of health professionals in our hospital and to determine the demographic characteristics that influence these behaviors. Materials and Methods: This study was carried out on 1679 health professionals who served as specialist doctors, assistant doctors, midwives, nurses and health technicians. Data was collected by questionnaire and Health-Promoting-Lifestyle-Profile-II (HPLP-II). On the days of data collection, 331 health care workers working in polyclinics, services and laboratories were reached ;the response rate was 96.6% (N=320). Results: 60.6% of health workers were women. The mean age was 33 ± 4.71 (17-59) years. Health promotion behavior of the health workers is at a moderate level (125.0 ±18.4) and the highest score was for spiritual growth subscale and the lowest score was for physical activity subscale. Nutrition subscales 40 for years and over age group were found to be significantly higher (p=0.005). Women received higher scores from overall scale and all subscales except physical activity and health responsibilities (p <0.05). Midwives-nurses recieved higher scores then assistant doctors in overall scale and health responsibilities subscale (p<0.001). Health professionals who perceived their health status excellent and very well recieved higher overall scale score than others (p<0.05). There was no significant difference by the presence of chronic illness in themselves or in their families of health workers in overall health improvement behaviors scale scores. Specialist and assistant doctors had a higher rate to cure themselves than the other occupations (p = 0.001). Conclusion: Health workers and hospital management whose primary task is to improve the health are role models for community and they should be encouraged to improve the level of health-promoting lifestyle.